2010
DOI: 10.1007/s11357-010-9198-9
|View full text |Cite
|
Sign up to set email alerts
|

Tight binding of proteins to membranes from older human cells

Abstract: The lens is an ideal model system for the study of macromolecular aging and its consequences for cellular function, since there is no turnover of lens fibre cells. To examine biochemical processes that take place in the lens and that may also occur in other long-lived cells, membranes were isolated from defined regions of human lenses that are synthesised at different times during life, and assayed for the presence of tightly bound cytosolic proteins using quantitative iTRAQ proteomics technology. A majority o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 55 publications
3
17
0
Order By: Relevance
“…Even though the lens membrane fractions have been washed by 8 M urea and 0.1 M NaOH, significant amounts of crystallins are still associated with the membrane as reported by Truscott et al 19 In the current work, aA-Crystallin and bB1-crystallin have the largest spectral counts. aB-, bA3-, bA4-, bB2-, bS-, cCand cD-Crystallins also have high spectral counts (see Supplementary Material and Supplementary Tables S1a, S1b, http://www.iovs.org/lookup/suppl/doi:10.1167/iovs.…”
Section: Lens Membrane Proteomesupporting
confidence: 60%
See 1 more Smart Citation
“…Even though the lens membrane fractions have been washed by 8 M urea and 0.1 M NaOH, significant amounts of crystallins are still associated with the membrane as reported by Truscott et al 19 In the current work, aA-Crystallin and bB1-crystallin have the largest spectral counts. aB-, bA3-, bA4-, bB2-, bS-, cCand cD-Crystallins also have high spectral counts (see Supplementary Material and Supplementary Tables S1a, S1b, http://www.iovs.org/lookup/suppl/doi:10.1167/iovs.…”
Section: Lens Membrane Proteomesupporting
confidence: 60%
“…15,16 Membrane proteins are normally underrepresented in the majority of proteome profiles due to their extreme hydrophobicity. 17,18 In addition, crystallins and high abundance cytoskeletal proteins such as filensin and CP49 are strongly associated with the membrane protein fraction, 19 resulting in the dilution of membrane protein signals. Recently, a membrane proteomics approach was utilized to produce descriptions of membrane signatures in the mouse lens fiber cells and 232 proteins were found enriched or unique in the lens membrane fraction.…”
Section: Discussionmentioning
confidence: 99%
“…The chaperone properties of alpha-crystallin are thought to allow the lens to tolerate aging-induced deterioration of the lens proteins without showing signs of cataracts until older age [9]. A majority of lens beta crystallins and all gamma crystallins are increasingly membrane bound with age, however, the chaperone proteins alpha A and alpha B crystallin, as well as the thermally-stable protein, B2 crystallin, are not associated with the membranes with age [228].…”
Section: Chaperone-like Function Of Alpha-crystallin and Its Domains mentioning
confidence: 99%
“…The α-crystallins influence the head group organization of the phospholipids (Zhu et al, 2010a). Other lens proteins also become associated as the membranes age (Truscott et al, 2011) and it is thought that this will also contribute to the complexity of the protein complement on the membranes in aged lenses. Zhao et al (2015) found that applying lanosterol, but not cholesterol, to the eyes of dogs with age related (non-diabetic) cataract, cells transfected with mutant αA-crystallin and to ex vivo cataractous rabbit lens resulted in solubilization of the cataracts and solubilisation of the protein aggregates.…”
Section: Dietary Factors Associated With Altered Lens Cataract Risksmentioning
confidence: 99%